Model Implementasi Kebijakan Pendidikan Berbasis Konteks Lokal di Kabupaten Seram Bagian Barat - Natalis Lemosol; Samson Laurens; Natanael Elake (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This article develops a local context-based education policy implementation model for West Seram Regency, Maluku Province. The study applies a qualitative case-study approach supported by in-depth interviews, participant observation, and document analysis involving education officials, school principals, teachers, supervisors, community leaders, customary actors, and parents. The findings show that education policy implementation in West Seram is shaped by four interrelated determinants: archipelagic geography, institutional capacity, socio-cultural resources, and human and financial resources. National education policies cannot be implemented effectively through a uniform model because schools in remote and island areas face limited transportation, electricity, internet connectivity, teacher distribution, and learning facilities. At the same time, local Maluku values such as pela gandong, masohi, and sasi provide cultural resources for strengthening character education, community participation, and culturally responsive pedagogy. Based on these findings, the article proposes the Local Context-Based Education Policy Implementation Model consisting of four integrated dimensions: policy adaptation, institutional strengthening, integration of local wisdom, and multi-actor collaboration. The model contributes to policy implementation studies by linking top-down policy standards with bottom-up contextual adaptation, particularly in archipelagic education governance.